Zsazsa Zaturnnah sa kalakhang Maynila #2 ng tatlong bahagi - Vergara, Carlo (Visprint, 2016)
Zsazsa Zaturnnah sa kalakhang Maynila is the sequel to the award-winning graphic novel. This is the second of three parts.